Etnomatematica: psicologia aplicada à educação matemática - Marabeli, Adriana [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Investigations in ethnomathematics show that there are several cultural forms of mathematics, mathematics different dominant. Currently, most research in ethnomathematics aim an ethnographic study of anthropological or cultural groups. However, there is a strong need for studies in ethnomathematics is to target the pedagogical action, involving the teachinglearning practices. So the big challenge for researchers in ethnomathematics is the development of study and teaching practices in line with the objectives philosophicaltheoretical Program Ethnomathematics

As investigações em etnomatemática evidenciam que há várias formas culturais de matemática, diferentes da matemática dominante. Atualmente, a maioria das pesquisas em etnomatemática, têm como objetivo um estudo etnográfico ou antropológico dos grupos culturais. Existe, porém, uma forte necessidade de que os estudos em etnomatemática se direcionem à ação pedagógica, envolvendo práticas de ensino-aprendizagem. Assim, o grande desafio para os pesquisadores em etnomatemática é a elaboração de estudo e práticas pedagógicas em conformidade com os objetivos filosófico-teóricos do Programa de Etnomatemática
Keywords: Matemática - Estudo e ensino; Etnomatematica